2007
DOI: 10.1128/aem.02944-06
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus rhamnosus Strain GG Reduces Aflatoxin B 1 Transport, Metabolism, and Toxicity in Caco-2 Cells

Abstract: The probiotic Lactobacillus rhamnosus GG is able to bind the potent hepatocarcinogen aflatoxin B 1 (AFB 1 ) and thus potentially restrict its rapid absorption from the intestine. In this study we investigated the potential of GG to reduce AFB 1 availability in vitro in Caco-2 cells adapted to express cytochrome P-450 (CYP) 3A4, such that both transport and toxicity could be assessed. Caco-2 cells were grown as confluent monolayers on transmembrane filters for 21 days prior to all studies. AFB 1 levels in cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
48
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(53 citation statements)
references
References 45 publications
4
48
0
Order By: Relevance
“…These data are consistent with other experimental studies which had evidenced the ability of lactobacilli and bifidobacteria to decrease the genotoxic activity of some chemical compounds [32,77,78]. Gratz et al [79] used DNA fragmentation as a marker of AFB 1 -induced DNA damage in differentiated Caco-2 cells exposed to AFB 1 following induction of CYP 3A4 . DNA damage was apparent following treatment with AFB 1 , while coincubation with LGG reduced the AFB 1 -induced damage in this test system.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These data are consistent with other experimental studies which had evidenced the ability of lactobacilli and bifidobacteria to decrease the genotoxic activity of some chemical compounds [32,77,78]. Gratz et al [79] used DNA fragmentation as a marker of AFB 1 -induced DNA damage in differentiated Caco-2 cells exposed to AFB 1 following induction of CYP 3A4 . DNA damage was apparent following treatment with AFB 1 , while coincubation with LGG reduced the AFB 1 -induced damage in this test system.…”
Section: Discussionsupporting
confidence: 80%
“…This might be, in part, due to the ability of lactic acid bacteria to adsorb this mycotoxin; where several studies clearly reported the adsorption mechanisms in vitro [24,79,89]. Previous work showed that LGG was the most efficient strain in binding a range of mycotoxins, including aflatoxins [27].…”
Section: Discussionmentioning
confidence: 99%
“…These epithelial cells are tightly bound by intercellular junctional complexes, which regulate the paracellular permeability, and thus maintain epithelial integrity. In confluent Caco-2 monolayers, a cell line that mimics the intestinal barrier, aflatoxin appears to affect the integrity of the monolayer by modulating paracellular transport (124) . Thus, aflatoxin may further exacerbate dietary restricted individuals, and perhaps prolong a cycle of poor nutrient retention, extended gastrointestinal infection, and enteropathy.…”
Section: Aflatoxin and Gastrointestinal Toxicitymentioning
confidence: 99%
“…There have been developments within bioremediation research to investigate the potential of transitory food-grade bacteria to prophylactically prevent the absorption of environmental toxins, such as pesticides (22), heavy metals (23), and aflatoxin (24,25). Many lactobacilli are commonly used in fermented foods, such as yogurt, cheese, sauerkraut, pickles, beer, wine, cider, kimchi, cocoa, and kefir (26).…”
mentioning
confidence: 99%